Turnover Intention pada Perusahaan Logistik - Simon Gultom; Euis Saribanon; Husni Hasan (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
The aim of this research is to perceive transformational leadership influence, organization commitment and job insecurity into turnover intention on PT. Birotika Semesta (DHL Express) Jakarta’s employees. Variable assesment using qustionnaire which distributed to 100 employees of PT. Birotika semesta (DHL Express) Jakarta. The analysis using statistical and result of the questionnaire statement are valid and reliable. Afterwards taking on BLUE tested, and multiple linear regression. Multiple linear regression results revealed that as a partial of each independent variable which transformational leadership, organization commitment, job insecurity are impact into turnover intention on PT. Birotika Semesta (DHL Express) Jakarta’s employee. Transformational leadership, organization commitment and job insecurity are impact simultaneously to turnover intention on PT. Birotika Semesta (DHL Express) Jakarta’s employee.